Quantifying episodes of sexual selection: Insights from a transparent worm with fluorescent sperm. (3rd February 2016) - Marie‐Orleach, Lucas; Janicke, Tim; Vizoso, Dita B.; David, Patrice; Schärer, Lukas
Abstract : Sexual selection operates through consecutive episodes of selection that ultimately contribute to the observed variance in reproductive success between individuals. Understanding the relative importance of these episodes is challenging, particularly because the relevant postcopulatory fitness components are often difficult to assess. Here, we investigate different episodes of sexual selection on the male sex function, by assessing how (precopulatory) mating success, and (postcopulatory) sperm‐transfer efficiency and sperm‐fertilizing efficiency contribute to male reproductive success. Specifically, we used a transgenic line of the transparent flatworm, Macrostomum lignano, which expresses green fluorescent protein (GFP) in all cell types, including sperm cells, enabling in vivo sperm tracking and paternity analysis. We found that a large proportion of variance in male reproductive success arose from the postcopulatory episodes. Moreover, we also quantified selection differentials on 10 morphological traits. Testis size and seminal vesicle size showed significant positive selection differentials, which were mainly due to selection on sperm‐transfer efficiency. Overall, our results demonstrate that male reproductive success in M. lignano is not primarily limited by the number of matings achieved, but rather by the ability to convert matings into successful fertilizations, which is facilitated by producing many sperm.